Barriers to cervical cancer screening in Africa: a systematic review - Fennie Mantula; Yoesrie Toefy; Vikash Sewram (BMC Public Health, 2024)
Abstract Introduction Africa has one of the highest burdens of cervical cancer in the world. The unacceptably high incidence and mortality rates could be reduced through implementing a comprehensive approach to its prevention and control that includes screening, which however, is low in most low-and-middle-income countries. Hence, this systematic review aims at exploring factors that prevent women from utilising cervical cancer screening services in the region. Methods A mixed method systematic review was conducted. A search was performed on PubMed (Medline), EMBASE, CINAHL (EBSCOHOST) and Scopus databases for articles published until May 2019 without time, language or study design limits. Two reviewers critically appraised the included studies independently using the standard quality assessment criteria for evaluating primary research papers. Results of the quantitative and mixed methods studies were transformed into qualitative data and synthesised using thematic analysis. Results From a potential 2 365 studies, 24 from 11 countries met the eligibility criteria and were selected; eight qualitative, 13 quantitative, and three that used the mixed-method approach. The primary barriers were identified as poor access to screening services, lack of awareness and knowledge on cervical cancer and screening, and socio-cultural influences. Service providers perceived lack of skills, screening equipment and supplies, and staff shortages as the major barriers to the provision of screening services. Conclusion Barriers to cervical cancer screening in Africa are multifaceted and require a holistic approach that will address them concurrently at the health system, individual, interpersonal, community and structural levels. Political will complimented by stakeholder involvement is required in the development and implementation of strategies that will ensure acceptability, availability, accessibility, and affordability of screening to minimise barriers in accessing the service.